To be or not to be: are cryopreserved embryos protected under the sharīʿah? - Zawawi, Majdah; Hussain, Bilal (USIM Press, 2024)
One of the main aims of the Sharīʿah (Maqāṣid al-Sharīʿah) is the protection of human life (Hifz al-Nafs). Advances in medical science have similar aims and have created technology to assist infertile couples to overcome their infertility. One of the technologies developed to further simplify this process is the ability to freeze excess embryos to be stored through cryopreservation that enables these embryos to be stored for long periods of time. This technology allows infertile couples to use these embryos when they opt for treatment not only once but several times. Despite this its benefits, the cryopreservation of embryos could bring about several legal issues. This study focuses on the legal status of cryopreserved embryos in two situations. The first is in the event of divorce between the parties and the second is in the event of death of one or both of the parties. The main concern in these two situations is does the couple have full authority to decide what happens to their embryos, even to the extent of allowing them to perish? Are cryopreserved embryos protected under the Sharīʿah? Hence, this paper analyzes the sanctity of human embryos within the Sharīʿah and legal frameworks in selected Muslim countries, with particular emphasis on issues of right to life and their potential legal repercussions on human society. Through a comparative approach, this paper aims to shed light on the ethico-legal complexities surrounding cryopreserved human embryos under the Sharīʿah.